Strategi Nafkah Masyarakat Petani Padi Pasca Penutupan Waduk Keuliling - Putri Ulfia Putri; Ibnu Phonna Nurdin (Indo Publishing, 2026)
The temporary closure of Keuliling Reservoir due to the implementation of the 21st National Sports Week (PON XXI) in Aceh-Sumut has directly impacted the agricultural activities in Gampong Baksukon, Kuta Cot Glie District, Aceh Besar Regency, especially for rice farmers. This study aims to identify the livelihood strategies employed by the rice farming community following the reservoir closure. This research uses a qualitative method with a case study approach. Observation, in-depth interviews, and documentation were used by the researcher as techniques for collecting research data. Informants were selected using purposive sampling totaling 12 people, including the village chief (Keuchik), male farmers, and female farmers who met the research criteria. The findings indicate three main livelihood strategies adopted by the community, based on Scoones’ Livelihood Strategies theory: (1) Livelihood resource engineering (intensification) through the use of water pump machines and additional family labor, which has not been fully effective due to limited facilities and high operational costs, (2) Livelihood diversification involving non-agricultural activities such as livestock farming, trading, daily labor, and laudry services, which proved effective in helping balance household income, and (3) spatial engineering (migration), mainly carried out bye younger family members migrating to cities to work and send remittances home. Diversification and migration strategies have been the most successful in maintaining the economic resilience of farming households during the water crisis. It is anticipated that the results of this study will be useful in developing policies for resilience livelihood and air pollution in the rural area.